2011
DOI: 10.25011/cim.v34i5.15674
|View full text |Cite
|
Sign up to set email alerts
|

Vascular progenitor recruitment in critically ill patients with acute kidney injury

Abstract: Purpose: Endothelial-like vascular progenitor cells (VPCs) are blood-derived angiogenic precursors that can facilitate vascular repair. The mobilization of peripheral blood VPCs and their role in recovery were investigated in patients with acute kidney injury (AKI) in the intensive care unit (ICU) setting. Methods: Blood samples were drawn on days 0, 3, 7 and 14 in 38 patients admitted to ICU: 30 with AKI and in eight controls with normal renal function. Circulating VPC levels were quantified by the early out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The significant advantage of ECFCs is that they can easily be isolated from adult peripheral blood, enabling auto-transplantation. Further, ECFC delivery has been characterized as suitable for application to a wide variety of tissues, including bone [ 11 , 12 ], kidney [ 13 , 14 ], and neural tissue [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significant advantage of ECFCs is that they can easily be isolated from adult peripheral blood, enabling auto-transplantation. Further, ECFC delivery has been characterized as suitable for application to a wide variety of tissues, including bone [ 11 , 12 ], kidney [ 13 , 14 ], and neural tissue [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of circulating endothelial progenitor cells (EPCs) by Asahara et al (3,4), and further data suggesting their participation in postnatal vasculogenesis, provides evidence for vascular regeneration. EPCs multiply and differentiate into vascular endothelial cells, which facilitate vascular repair (5). Studies have revealed that EPCs differentiate into mature endothelial cells, involved in the repair of damaged endothelial cells.…”
Section: Introductionmentioning
confidence: 99%